UPPER CRETACEOUS AMMONITE ZONATION OF EASTERN CENTRAL ASIA - Khakimov F.Kh. (My University, 1998)
This paper presents a new detailed ammonite-based biostratigraphic zonation of the Upper Cretaceous in eastern Central Asia and substantially refines the previous scales. Two units were established in the lower Cenomanian: the Mediasiceras beljakovae and Karamaites gaurdakense beds. The middle Cenomanian comprises three units: the Mediasiceras lenticulare (Luppov) Beds, the Kopetdagites aktaschensis Zone, and the Acanthoceras jukesbrownei Zone. The upper Cenomanian includes the Eucalycoceras pentagonum and Sciponiceras gracile zones. In the lower Turanian, the Watinoceras coloradoense and Thomasites koulabicus zones are distinguished. The middle Turanian is divided into the Spathites (Jeanrogericeras) reveliereanum and Colllignoniceras woolgari zones. The upper Turanian corresponds to three units: the Subprionocyclus neptuni and Hourcquia pacifica zones and the Coilopoceras gissarensis beds. The Stantonoceras guadalupae and Stantonoceras polyopsis zones are recognized in the lower Santonian, and the local Asiatostantonoceras tagamense Zone is established in the upper Santonian. The lower Campanian corresponds to the single Scaphites inflatus Zone, whereas the upper Campanian is sudivided into the Hopliplacenticeras marroti and Trachyscaphites pulcherrimus zones. The Nostoceras hyatti and Baculites knorrianum zones are identified in the lower Maastrichtian. The lower boundary of the Maastrichtian is placed at a significantly lower level as compared with the previous scales. All the defined units are correlated to stage stratotypes and stratigraphic schemes of the adjacent regions.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая